POLA MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI KEPRIBADIAN GURU - Lailatilfadla, Sarah; Akmalia, Rizki; Hasri, Reihan Kamila; Putri, Eliza; Sovia Br Situmorang, Heni (IKAMAS: Manajemen Pendidikan Islam, 2022)
This study aims to examine the pattern of principal management in improving the personality competence of teachers in elementary schools. This study uses a qualitative approach. For information on this research data, researchers took several sources of information from the Principal at SD Terpadu Muhammadiyah 36 Medan. The results showed that the principal's management pattern in improving the teacher's personality competence at SD Terpadu Muhammadiyah 36 Medan was by planning a program to increase teacher personality competence, implementing a program to increase teacher personality competence and evaluating the program to increase teacher personality competence at SD Terpadu Muhammadiyah 36 Medan. The increase in teacher personality competence is carried out because the teacher is a role model for his students, therefore the teacher must have a good personality as an educator. In improving the personality competence of teachers at SD Terpadu Muhammadiyah 36 Medan, the principal applies Islamic values ​​sourced from the Qur'an and sunnah. After the implementation of the teacher personality competency improvement program, the principal then conducts an evaluation to review or ascertain whether the teacher's personality competence at SD Terpadu Muhammadiyah 36 Medan has increased or not and provides advice and motivation to teachers.